The Relationship Between Student Learning Styles and Student Learning Outcomes on Prophetic Da'wah Material in Class X PPLG SMKTI Muhammadiyah Cikampek - Fauziah Salsabila Waraow; Achmad Junaedi Sitika; Nurhasan Nurhasan (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the relationship between learning styles and student learning outcomes on the Prophet Muhammad's da'wah material in class X PPLG SMKTI Muhammadiyah Cikampek. The method used in this study is a quantitative method with a correlation approach. The population in this study were students of class X PPLG by taking samples from the entire population, namely as many as 60 respondents. Data collection was taken from a learning style questionnaire according to Bobbi De Porter and Mike Hernacki. The results of research on the relationship between learning styles and learning outcomes are: 1). There is a relationship between Learning Style (X) and Learning Outcomes (Y) with a significance value of 0.000 0.05 and a correlation value of Learning Style variable (X) of 0.705. This indicates that the degree of relationship between Learning Style variable (X) and Learning Outcomes (Y) is strongly correlated. 2). The learning style of class X PPLG SMKTI Muhammadiyah Cikampek is dominant in the auditory learning style with a large percentage obtained as much as 70%